Comparative effects of nutraceuticals on body weight in adults with overweight or obesity: A systematic review and network meta-analysis of 111 randomized clinical trials - Hossein Shahinfar; Ahmad Jayedi; Kimia Torabynasab; Nastaran Payandeh; Fahimeh Martami; Hanieh Moosavi; Elham Bazshahi; Sakineh Shab-Bidar (Elsevier, 2023)
There is no research on the comparative effects of nutraceuticals on weight loss in adults with overweight or obesity. This study aimed at quantifying and ranking the effects of different nutraceuticals on weight loss. We searched PubMed, Scopus, and Web of Science to November 2022. We included randomized trials evaluating the comparative effects of two or more nutraceuticals, or compared a nutraceutical against a placebo for weight loss in adults with overweight or obesity. We conducted random-effects network meta-analysis with a Frequentist framework to estimate mean difference [MD] and 95% confidence interval [CI] of the effect of nutraceuticals on weight loss. One hundred and eleven RCTs with 6171 participants that investigated the effects of 18 nutraceuticals on body weight were eligible. In the main analysis incorporating all trials, there was high certainty of evidence for supplementation of spirulina (MD: -1.77 kg, 95% CI: -2.77, -0.78) and moderate certainty of evidence that supplementation of curcumin (MD: -0.82 kg, 95% CI: -1.33, -0.30), psyllium (MD: -3.70 kg, 95% CI: -5.18, -2.22), chitosan (MD: -1.70 kg, 95% CI: -2.62, -0.78), and Nigella sativa (MD: -2.09 kg, 95%CI: -2.92, -1.26) could result in a small improvement in body weight. Supplementations with green tea (MD: -1.25 kg, 95%CI: -1.68, -0.82) and glucomannan (MD: -1.36 kg, 95%CI: -2.17, -0.54) demonstrated small weight loss, also the certainty of evidence was rated low. Based on our findings, supplementations with nutraceuticals can result in a small weight loss in adults with overweight or obesity.